The informal sector and microfinance institutions in West Africa - Webster, Leila; Fidler, Peter (Washington, D.C. : World Bank, 1996)
This book examines the dynamics and constraints faced by informal sectors in 12 West African countries -Burkina Faso, Cape Verde, Chad, the Gambia, Guinea, Guinea-Bissau, Mali, Mauritania, Niger, Sao Tome and Principe, Senegal, and Sierra Leone- as well as the issues confronted by the microfinance institutions that serve them. Nine microfinance companies considered to be among the most effective in the region were selected and evaluated for their suitability for partnership with the Bank. The book sums up major findings of the country profiles and of the institutional case studies, and lays out a series of options for World Bank involvement. Among the major findings are that informal sectors are very large and appear to be growing rapidly, accounting for one-third to three-quarters of total employment in most countries.
Includes bibliographical references (p. 333-338).
lje 11/07/2016
Loans
Keywords: Microfinance; Informal sector (Economics); Banks and banking; Banks and banking, Cooperative; Microfinance; Africa - french speaking West